2020
DOI: 10.3390/en13143538
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Performance of Grounding Device with Spike Rods (GDSR) with the Effects of Soil Resistivity and Configurations

Abstract: In a recently published work, the characteristics of a new grounding device with spike rods (GDSR) with various arrangements of ground electrodes under high magnitude impulse currents (up to 16 kA), was investigated. In an earlier study, the ground electrodes were installed in low resistivity test media, with resistance at steady state (Rdc) values ranging from 11 Ω to 75 Ω. In practice, various soil resistivity, ranging from a few Ohm-metres to several kiloOhm-metres, have been reported in the standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
2
18
0
Order By: Relevance
“…When developing a TL, tower footing resistance is one of the important parameters to be considered. The outcome of the improvement in the TFR depends on many factors, including the earth structure and soil resistivity, among others [15][16][17][18][19]. The arrangement of the earthing design usually has a relationship with the form of the configuration or tower footing.…”
Section: Countrymentioning
confidence: 99%
“…When developing a TL, tower footing resistance is one of the important parameters to be considered. The outcome of the improvement in the TFR depends on many factors, including the earth structure and soil resistivity, among others [15][16][17][18][19]. The arrangement of the earthing design usually has a relationship with the form of the configuration or tower footing.…”
Section: Countrymentioning
confidence: 99%
“…Along with these parameters of impedances, current rise and discharged times have also been analyzed and presented for various electrode's configurations and impulse polarity [6][7][8][9]. Current rise time is defined as the time taken for the current to reach its peak value, while the current discharged time is the time taken for the current to discharge to ground.…”
Section: Introductionmentioning
confidence: 99%
“…Current rise time is defined as the time taken for the current to reach its peak value, while the current discharged time is the time taken for the current to discharge to ground. It was discussed in the field experimental work [4,7,10] that the current rise times are an indication of the presence of inductive effect in the ground electrode, and were studied for a range of configurations, soil resistivity and stress. Harid et al [4] found that the longer the vertical rods and horizontal electrodes, the slower the current rise times were.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations